Mandible and iliac osteoblasts exhibit different Wnt signaling responses to LMHF vibration - Anute Pravitharangul; Srisurang Suttapreyasri; Chidchanok Leethanakul (Elsevier, 2019)
Objective: The jaw bones and long bones have distinct developmental origins and respond differently to mechanical stimuli. This study aimed to compare the Wnt signaling responses of human mandible osteoblasts and long bone osteoblasts to low-magnitude, high-frequency (LMHF) mechanical vibration in vitro. Methods: Primary human osteoblast cultures were prepared from mandibular bone (n = 3) and iliac bone (n = 3) specimens (six individuals). Osteoblast cell lines were subjected to vibration (0, 30, 60, 90, or 120 Hz) for 30 min. After 24 h, cells were vibrated for 30 min again, then harvested immediately to quantify Wnt10b, Wnt5a and runt-related transcription factor 2 (RUNX2) mRNA expression, β-catenin protein expression and alkaline phosphatase (ALP) activity. Results: Mandible and iliac osteoblasts responded differently to LMHF vibration: Wnt10b mRNA was upregulated by the frequency range tested; Wnt5a, β-catenin protein expression and RUNX2 mRNA expression were not altered. Furthermore, vibration upregulated ALP activity in mandible osteoblasts, but not in iliac osteoblasts. Conclusions: This study demonstrates mandible osteoblasts and long bone osteoblasts respond differently to LMHF mechanical vibration in terms of Wnt signaling expression and ALP activity. Therefore, the effects of whole-body vibration on the long bones cannot be generalized to the jaw bones. Furthermore, osteoblast-like cells mediate the cellular responses to vibration, at least in part, by secreting extracellular signaling molecules.